2021
DOI: 10.3389/fevo.2021.626442
|View full text |Cite
|
Sign up to set email alerts
|

Pipefish Locally Adapted to Low Salinity in the Baltic Sea Retain Phenotypic Plasticity to Cope With Ancestral Salinity Levels

Abstract: Genetic adaptation and phenotypic plasticity facilitate the migration into new habitats and enable organisms to cope with a rapidly changing environment. In contrast to genetic adaptation that spans multiple generations as an evolutionary process, phenotypic plasticity allows acclimation within the life-time of an organism. Genetic adaptation and phenotypic plasticity are usually studied in isolation, however, only by including their interactive impact, we can understand acclimation and adaptation in nature. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…In times of environmental change, we predict that altered interactions and co‐evolutionary dynamics between phages and bacteria will also change higher order interactions, which are often mediated by phages (Wendling, 2023; Wendling et al, 2017). This can be further intensified when fast changes in abiotic parameters, such as salinity, require recourse allocation towards respective coping mechanisms, that is osmoregulation in host organisms, which impairs their immune systems and ultimately increases the impact of infections (Goehlich et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…In times of environmental change, we predict that altered interactions and co‐evolutionary dynamics between phages and bacteria will also change higher order interactions, which are often mediated by phages (Wendling, 2023; Wendling et al, 2017). This can be further intensified when fast changes in abiotic parameters, such as salinity, require recourse allocation towards respective coping mechanisms, that is osmoregulation in host organisms, which impairs their immune systems and ultimately increases the impact of infections (Goehlich et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the observed changes seem to be species, tissue and immune factor dependent. A few studies have indicated an acclimation and adaptation potential of fish immunity to salinity [132][133][134] ( possibly driven by genetic and epigenetic changes, see §4), hence chronic exposure studies are needed to study long-term salinity effects on disease susceptibility. Data in this area of ecoimmunology are still limited but by applying more standardized methods (see suggestions in §6) it may be possible to decipher general effects in future research.…”
Section: (D) Salinitymentioning
confidence: 99%
“…Trans-generational plasticity provides an evolutionary opportunity for short-term acclimatization to changing environmental conditions by shaping the offspring phenotype through the transfer of parental experience (1)(2)(3)(4). Trans-generational plasticity can be adaptive and improve offspring survival in situations of rapid but predictable changes in abiotic conditions (e.g., temperature & salinity in marine habitats (5)(6)(7)(8)(9)(10)) as well as biotic conditions (e.g., changing microbial assemblage) in a matching parent-offspring environment (4,11,12). In the latter situation, trans-generational immune priming (TGIP; the transfer of parental immunological experience) was suggested to enhance offspring immune responses towards an infectious agent that parents have previously encountered.…”
Section: Introductionmentioning
confidence: 99%
“…A mismatch in the microbial assemblage between paternal and offspring environments, as well as a change of an additional abiotic environmental factor across generation, can induce costs of parentally-influenced constitutively upregulated immune responses in the offspring (48,49). While the latter may negatively influence offspring performance, TGIP that relies on inducible immune responses, might become ineffective when additional environmental factors change across generations, due to the resource-allocation trade-off involved (6,50,51). Disentangling constitutive from inducible influences of paternal immunological priming on offspring immune responses can thus illuminate how animals cope in a world of global change where emerging diseases can be a result of rapidly changing abiotic conditions.…”
Section: Introductionmentioning
confidence: 99%